Lactobacillus sp. for the Attenuation of Metabolic Dysfunction-Associated Steatotic Liver Disease in Mice - Titilayo Olotu; Jessica M. Ferrell (Microorganisms)
Probiotics are studied for their therapeutic potential in the treatment of several diseases, including metabolic dysfunction-associated steatotic liver disease (MASLD). Part of the significant progress made in understanding the pathogenesis of steatosis has come from identifying the complex interplay between the gut microbiome and liver function. Recently, probiotics have shown beneficial effects for the treatment and prevention of steatosis and MASLD in rodent models and in clinical trials. Numerous studies have demonstrated the promising potential of lactic acid bacteria, especially the genus Lactobacillus. Lactobacillus is a prominent bile acid hydrolase bacterium that is involved in the biotransformation of bile acids. This genus’ modulation of the gut microbiota also contributes to overall gut health; it controls gut microbial overgrowth, shapes the intestinal bile acid pool, and alleviates inflammation. This narrative review offers a comprehensive summary of the potential of Lactobacillus in the gut-liver axis to attenuate steatosis and MASLD. It also highlights the roles of Lactobacillus in hepatic lipid metabolism, insulin resistance, inflammation and fibrosis, and bile acid synthesis in attenuating MASLD.